ANALISIS BIAYA DAN PENDAPATAN USAHATANI KENTANG DESA SINISIR KECAMATAN MODOINDING (Costs and Income Analysis of Potato Farming in Sinisir Village, Modoinding District) - Kezia Mokalu; Mex F. L. Sondakh; Juliana R. Mandei (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
This study aims to determine the costs and income of potato farming in Sinisir Village, Modoinding District. The research was conducted from October 2021 to December 2021. The data used in this study were primary data and secondary data and then analyzed descriptively. The results showed that the total average production cost incurred by potato farmers was IDR 24,437,838 per hectare with an average total revenue of IDR 53,603,424 per hectare. So, the average income on potato farming was IDR 29,165,586 per hectare.